2020
DOI: 10.1111/iwj.13461
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on pressure injury preventative interventions by risk level for critically ill patients: A modified Delphi study

Abstract: The aim of this modified Delphi study was to determine a minimum pressure injury preventative intervention set for implementation relative to critically ill patients' risk level. Preventative interventions were identified via systematic review, risk levels categorised by an intensive‐care‐specific risk‐assessment‐scale (COMHON Index), and panel members (n = 67) identified through an international critical care nursing body. Round 1: panel members were asked to rate implementation of 12 interventions according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…We also agree with the international guideline 7 statement, "Do not rely on a total risk assessment tool score alone as a basis for risk based prevention" (p. 60). Accordingly, in our paper, 1 Our approach has been to develop evidence, based on international expert consensus, using a formal and rigorous research method, as described in our paper (p. 1114). 1 In the intensive care setting, our results demonstrated expert consensus that as risk level increases, so too should the number and intensity of preventative interventions.…”
Section: Dear Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also agree with the international guideline 7 statement, "Do not rely on a total risk assessment tool score alone as a basis for risk based prevention" (p. 60). Accordingly, in our paper, 1 Our approach has been to develop evidence, based on international expert consensus, using a formal and rigorous research method, as described in our paper (p. 1114). 1 In the intensive care setting, our results demonstrated expert consensus that as risk level increases, so too should the number and intensity of preventative interventions.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Accordingly, in our paper, 1 Our approach has been to develop evidence, based on international expert consensus, using a formal and rigorous research method, as described in our paper (p. 1114). 1 In the intensive care setting, our results demonstrated expert consensus that as risk level increases, so too should the number and intensity of preventative interventions. This is also consistent with our previous findings, which indicated that as risk level increases, nurses prescribe (plan) more preventative interventions.…”
Section: Dear Editorsmentioning
confidence: 99%
“…11 Five to fifteen experts are considered adequate to achieve content validity. 12,13 Delphi processes have previously been used to inform critical care practice including management of COVID-19, 14 preventing pressure injury 15 and identifying core outcome measures after respiratory failure. 16 The aim of this study was to gather expert consensus to identify important risk factors for NOAF during critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editors, With great interest, we read the recent paper by Lovegrove et al who developed pressure injury (PI) preventive interventions based on risk categories of the Consciousness, Mobility, Heamodynamics, Oxygenation, Nutrition (COMHON) Index. 1 PI prevention in clinical practice is a complex and challenging task, and initiatives aimed at guiding and improving setting-specific PI prevention are highly welcome. Because the authors use the latest International Guideline for prevention and treatment of PIs 2,3 as background for their work, some assumptions and statements should be put into context: First, citing the International Guideline, 3 the authors state: "PI prevention begins with risk assessment, which should be undertaken using a structured risk assessment scale combined with clinical judgement."…”
mentioning
confidence: 99%
“…Because the authors use the latest International Guideline for prevention and treatment of PIs 2,3 as background for their work, some assumptions and statements should be put into context: First, citing the International Guideline, 3 the authors state: "PI prevention begins with risk assessment, which should be undertaken using a structured risk assessment scale combined with clinical judgement." 1 We would like to clarify that such a statement does not exist in the International Guideline. 3 We feel very concerned about this wrong and misleading citation, which Lovegrove et al 1 used to justify their risk assessment approach.…”
mentioning
confidence: 99%